2012
DOI: 10.5012/bkcs.2012.33.7.2274
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Degradation of Phenol and 2-Chlorophenol Using Pt/Ti and Boron-Doped Diamond Electrodes

Abstract: To test the efficiency of the BDD electrode for complete mineralization of organic wastewater, phenol and 2-chlorophenol (2-CP) were treated electrochemically with both an active Pt/Ti electrode and a nonactive boron doped diamond (BDD) electrode, respectively, in neutral aqueous medium. Aqueous solutions of both phenol and 2-chlorophenol were treated electrochemically using an in-house fabricated flow through electrochemical cell (FTEC). The experimental variables included current input, treatment time, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 21 publications
0
11
1
Order By: Relevance
“…In indirect anodic electro-oxidation, anodically generated chlorine and hypochlorite are used as the oxidizing agents for the decomposition of organics in the presence of chloride ions [38]. As the influent of our experimental domestic wastewater contained 43 mg/L of initial chloride ions and because the Pt/Ti anode used in our experiment was an 'active' electrode [39,40], we believe that the decomposition and the oxidation of organics (R) and removal of COD were due to indirect anodic oxidations and active chlorine-mediated reactions. An increase in voltage leads to an increase in current density and an increased current density increases charge loading, which in turn increases the pollutant removal efficiency [41].…”
Section: Cod Removalmentioning
confidence: 99%
“…In indirect anodic electro-oxidation, anodically generated chlorine and hypochlorite are used as the oxidizing agents for the decomposition of organics in the presence of chloride ions [38]. As the influent of our experimental domestic wastewater contained 43 mg/L of initial chloride ions and because the Pt/Ti anode used in our experiment was an 'active' electrode [39,40], we believe that the decomposition and the oxidation of organics (R) and removal of COD were due to indirect anodic oxidations and active chlorine-mediated reactions. An increase in voltage leads to an increase in current density and an increased current density increases charge loading, which in turn increases the pollutant removal efficiency [41].…”
Section: Cod Removalmentioning
confidence: 99%
“…It has been found that several chemical oxidants such as ferrate (K 2 FeO 4 ), permanganate (KMnO 4 ), and manganese oxides (MnO 2 ) also effectively degrade triclosan, but they lead to coloration and sludge formation in the treated water. Previous reports showed that triclosan can be degraded by electrochemical process using screen‐printed carbon electrode, mercury cathode, and boron‐doped diamond (BDD) electrode , while some other organic substances also undergo mineralization on the high oxygen over‐potential BDD anode . Despite the BDD electrode having an excellent stability with high oxygen evolution over‐potential (OEOP) towards organic oxidation, its high cost and normally the difficulties to find an appropriate substrate for deposition of the diamond layer limits the large‐scale application .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, comparative studies in electrodes combinations were described: Yoon et al (2012) reported a flow reactor for the electrochemical degradation of phenol and 2-chlorophenol using Pt/Ti and BDD electrodes, as well as Ambauen et al (2019) comprised a electrochemical oxidation batch reactor for salicylic acid degradation with BDD and Pt electrodes. In both studies similar removal rates in the different electrodes combinations were attained, showing that not only the electrodes type highly influence the compounds degradation efficiencies, but also the physicochemical characteristics of the contaminants to be degraded.…”
Section: Introductionmentioning
confidence: 99%
“…In both studies similar removal rates in the different electrodes combinations were attained, showing that not only the electrodes type highly influence the compounds degradation efficiencies, but also the physicochemical characteristics of the contaminants to be degraded. BDD and MMO have been mainly and equally used as anodes (Moreira et al, 2017), both showing similar performances in the degradation efficiency (Brillas and Martínez-Huitle, 2015;Skoumal et al, 2008;Yoon et al, 2012). BDD was reported as electrochemical inactivator of phenolic compounds (Sirés et al, 2007;Wang and Farrell, 2004), and Ti/MMO was used to degrade organic contaminants in wastewater (Yuan et al, 2013).…”
Section: Introductionmentioning
confidence: 99%